Investigation of the imaging characteristics of the ALBIRA II small animal PET system for 18F, 68Ga and 64Cu - Attarwala, Ali Asgar; Wängler, Björn; Glatting, Gerhard (Zeitschrift für medizinische Physik, 2017)
Aim: In this study the performance characteristics of the Albira II PET sub-system and the response of the system for the following radionuclides 18F, 68Ga and 64Cu was analyzed. Materials and methods: The Albira II tri-modal system (Bruker BioSpin MRI GmbH, Ettlingen, Germany) is a pre-clinical device for PET, SPECT and CT. The PET sub-system uses single continuous crystal detectors of lutetium yttrium orthosilicate (LYSO). The detector assembly consists of three rings of 8 detector modules. The transaxial field of view (FOV) has a diameter of 80mm and the axial FOV is 148mm. A NEMA NU-4 image quality phantom (Data Spectrum Corporation, Durham, USA) having five rods with diameters of 1, 2, 3, 4 and 5mm and a uniform central region was used. Measurements with 18F, 68Ga and 64Cu were performed in list mode acquisition over 10h. Data were reconstructed using a maximum-likelihood expectation-maximization (MLEM) algorithm with iteration numbers between 5 and 50. System sensitivity, count rate linearity, convergence and recovery coefficients were analyzed. Results: The sensitivities for the entire FOV (non-NEMA method) for 18F, 68Ga and 64Cu were (3.78±0.05)%, (3.97±0.18)% and (3.79±0.37)%, respectively. The sensitivity based on the NEMA protocol using the 22Na point source yielded (5.53±0.06)%. Dead-time corrected true counts were linear for activities ≤7MBq (18F and 68Ga) and ≤17MBq (64Cu) in the phantom. The radial, tangential and axial full widths at half maximum (FWHMs) were 1.52, 1.47 and 1.48mm. Recovery coefficients for the uniform region with a total activity of 8MBq in the phantom were (0.97±0.05), (0.98±0.06), (0.98±0.06) for 18F, 68Ga and 64Cu, respectively. Conclusion: The Albira II pre-clinical PET system has an adequate sensitivity range and the system linearity is suitable for the range of activities used for pre-clinical imaging. Overall, the system showed a favorable image quality for pre-clinical applications.